Optimal physical and nutrient parameters for growth of trichoderma virens UKMP-1M for heavy crude oil degradation (Pengoptimuman Parameter Fizikal dan nutrien bagi pertumbuhan trichoderma virens UKMP-1M untuk degradasi minyak mentah berat) - Ainon Hamzah; Mazni Abu Zain; Othman Omar; Sahidan Senafi (Universiti Kebangsaan Malaysia, 2012)
This study was carried out to determine the optimal parameters for the production of biomass of Trichoderma virens UKMP-1M, a fungus isolated from oil-polluted wastewater. The isolate showed maximum growth at day six after incubation in Mineral Salt Medium (MSM) in the presence of 3% (v/v) heavy Khefji Sour crude oil. Although it grew at pH between 5.0 and 7.0, it grew best at pH 5.5. T. virens UKMP-1M grew at temperatures between 25°C and 35°C, with its highest growth at 30°C. Aeration by agitation at 200 rpm was shown to yield the greatest biomass. Peptone at concentration of 1.5% (w/v) was determined to be a better nitrogen source than urea, potassium nitrate (KNO3), yeast extract, ammonium sulphate ((NH4)2SO4) and ammonium chloride (NH4Cl). Addition of 1% (v/v) crude oil to the MSM medium led to higher biomass production than the addition of 3%, 5%, 7% and 10% (v/v) crude oil. The result also revealed that 40% of total petroleum hydrocarbon (TPH), 100% of pristane and 74% of phytane compounds were degraded after 9 days of incubation at optimal physical and nutrient parameters.